Gambaran Swamedikasi Pada Mahasiswa di Indonesia - Angga Dwi Prasetyo (Herbal Medicine Journal, 2023)
Self-medication can be interpreted as the treatment of all diseases that exist within oneself through simple medicines. Someone who uses self-medication when "diagnosing" a condition must be able to understand how to use drugs according to the patient's condition. People who carry out self-medication when "diagnosing" a disease, must be able to understand the benefits of the drug so that the drug used is proportional to the patient's condition. This literature review aims to find out what self-medication is like for students in Indonesia. The author uses the literature review study method, related to the description of self-medication in students in Indonesia from various journals, including international journals that have been published in 2016-2023 and are indexed on Google Schoolar. The results of the literature study show that health students have good knowledge and patterns of self-medication. The conclusion is that health students have better knowledge than non-health students because health students gain knowledge about self-medication during lectures.